Studi Literatur Analisis Perbandingan Arsitektur Permainan Komputer PES 2018 vs FIFA 18 - Bima Dirgantara, Harya; Septanto, Henri (KALBISCIENTIA Jurnal Sains dan Teknologi, 2019)
This literature study discusses the comparison of computer game architecture between PES 2018 and FIFA 18. Both of these games are similar and have fanbase of their respective players. This football game is popular and f amous in the world. Although both are football games, but there are differences in the architecture. Game architecture in this context is the concept of the game, using reusability, determine granularity, risk bugs, and do localization. Every aspect of the architecture has an impact and influence on the end result of computer games. In the end each computer game has its own uniqueness.